2014
DOI: 10.1021/am5019429
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Silsequioxane-Derived Si/SiOx Nanospheres for High-Capacity Lithium Storage Materials

Abstract: Si/SiOx composite materials have been explored for their commercial possibility as high-performance anode materials for lithium ion batteries, but suffer from the complexity of and limited synthetic routes for their preparation. In this study, Si/SiOx nanospheres were developed using a nontoxic and precious-metal-free preparation method based on hydrogen silsesquioxane obtained from sol-gel reaction of triethoxysilane. The resulting Si/SiOx nanospheres with a uniform carbon coating layer show excellent cycle p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 98 publications
(100 citation statements)
references
References 35 publications
2
95
0
Order By: Relevance
“…This is an innovative approach to developing a new energy technology, which directly converts mechanical energy into electrochemical energy without energy being wasted on the outer circuitry and decreases energy conversion loss. Importantly, the development of both high performance energy storage devices [208][209][210][211][212][213][214] and the materials [215][216][217][218][219][220][221][222] used in the devices is essential for the fabrication of highly effective hybridized "all-in-one energy harvesting and storage devices" in the future.…”
Section: Simple Connection Of Energy Harvester and Storage Devicementioning
confidence: 99%
“…This is an innovative approach to developing a new energy technology, which directly converts mechanical energy into electrochemical energy without energy being wasted on the outer circuitry and decreases energy conversion loss. Importantly, the development of both high performance energy storage devices [208][209][210][211][212][213][214] and the materials [215][216][217][218][219][220][221][222] used in the devices is essential for the fabrication of highly effective hybridized "all-in-one energy harvesting and storage devices" in the future.…”
Section: Simple Connection Of Energy Harvester and Storage Devicementioning
confidence: 99%
“…Figure 11 illustrates the corresponding surface morphology of these electrodes as determined by SEM. [33,37] The bands at 870, 1490, and 1530 cm À1 are typical of Li 2 CO 3 ,w hereas the bands at 1170, 1314, 1397, and 1638 cm À1 are characteristic of the lithium alkycarbonates (ROCO 2 Li and ROLi). [33,37] The bands at 870, 1490, and 1530 cm À1 are typical of Li 2 CO 3 ,w hereas the bands at 1170, 1314, 1397, and 1638 cm À1 are characteristic of the lithium alkycarbonates (ROCO 2 Li and ROLi).…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…It was found that the thickness of the composite anode increased by 30 %f rom 8.0 to 10.4 mm after 100 cycles, which is ac onsiderably low value compared with previously reported Si based anodes. [13,24,40,41] To examine the thermal stability of the 36 h-milled composite anode,i t was subjected to differential scanningc alorimetry (DSC) analysis after it wasc harged to 0.001 Vv ersusL i/Li + (i.e., in af ully lithiated state) and results are shown in Figure 7c and d. From the comparison, we can see that the heat flow in the DSC profile of the composite anode was much smaller than that in Si nanoparticles and even smaller still than that in ac ommercial graphite anode.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] For several decades since the first demonstration of electrochemical reactivity of Si oxidesw ith Li + in organic electrolytes, stoichiometric silica (SiO 2 )w as not considered electrochemically active with Li + because of its high thermodynamic stability.H owever,i n2 001, it was reported that nanosized SiO 2 can in fact react with Li + reversibly, [28] leadingt os everal studies into the reactivity of amorphous and/or nanostructured SiO 2 . [15][16][17] More recently,C hang et al demonstrated that mechanically ball-milled SiO 2 exhibits ar eversible capacity of about 800 mAh g À1 and displaysa ne xcellent capacity retention over 100 cycles without any external buffering or ac onductive medias uch as carbon.…”
Section: Introductionmentioning
confidence: 99%